Health Education Intervention on Husbands’ Perception Towards Participation in Reproductive Health Services - Muhammad Sani, Hadiza; Haruna Ibrahim , Abdullahi (Indonesian Contemporary Nursing Journal (ICON Journal), 2024)
Aims: The study was conducted to determine the effect of husbands' participation in reproductive health education on the spousal utilization of maternal health services in Kaduna North Senatorial District, Kaduna state. Methods: A Quasi-experimental study design was used. The study group had a pre-intervention followed by an intervention (health education) of two sessions which lasted for thirty minutes each with an interval of four weeks between them. Then a post-intervention test after nine months. The researcher used a multistage sampling technique in the selection of towns and a systematic sampling technique for the selection of participants, a questionnaire was used to collect data. Results: The result shows a statistically significant positive change in husbands’ perception regarding participation in their spouses’ utilization of reproductive health services (p<0.05) with mean change from 2.79±0.405 pre-intervention to 3.11±0.540 post-intervention. Conclusion: As a promising approach, the intervention improved husbands’ perception of participation in spouses’ utilization of reproductive health service. The study recommended the integration of a module on husbands' participation in reproductive health services in the healthcare packages for prospective husbands and those with wives as well as those cohabiting to improve their perception and participation in reproductive health services.